Komparasi Kurikulum Terpadu Pendidikan Agama Islam Pada Sekolah Menengah Pertama Islam Boarding Di Yogyakarta - Lely Nur Hidayah Syafitri (Universitas Cokroaminoto Yogyakarta, 2019)
The curriculum is a strategic element in an education program, which is expected to produce good educational products, some private schools are looking for an alternative in the effort to develop the curriculum, one of which uses Special curriculum, suggestions produce quality students. To achieve this it takes hard work and maximum effort. The curriculum used in SMP IT Abu Bakar Yogyakarta is a Diknas curriculum combined with a special curriculum that is integrated Islamic Curriculum (IT), through this curriculum is expected that teachers can embed Islamic character values in learners Through several learning activities in class and outside classes such as coaching through mentoring, memorization of the Qur'an, and giving motive. Meanwhile, in MTs Ibnul Qoyyim Putri Yogyakarta use the curriculum of Depag, Diknas curriculum, and refers to the curriculum of Pondok Modern Darussalam Gontor, the flagship program emphasized in MTs Ibnul Qoyyim Putri Yogyakarta is foreign language ability, namely Arabic and English.